Evaluación de la Calidad del agua para consumo humano por medio de un laboratorio móvil - Mack, Yazmin; Olmos, Jorge; Broce, Kathia; Gómez, Natasha; Henríquez, Dina (Congreso Nacional de Ciencia y Tecnología - APANAC, 2023)
Due to uncertainty about the quality of water for human consumption in Tonosí, Los Santos province; the project “Morbidity vs the quality of water for human consumption in Tonosí: a pilot study” is carried out, which aims to evaluate water quality including the identification and quantification of unconventional parameters such as heavy metals and organic compounds in remote areas, with advanced instrumental analytical techniques by means of a mobile laboratory operated by qualified technical personnel. The mobile laboratory is a van-type vehicle that is equipped with compact equipment, with state-of-the-art technology, quick response and with a minimum of waste generated. Thanks to this equipment, it is possible to evaluate organic compounds by chromatography; heavy metals by X-ray fluorescence; biological contamination using a membrane filtration technique; physicochemical parameters by titrimetry and spectrophotometry; in addition to the evaluation of environmental conditions. In this way, this study seeks to respond to the concern of the population regarding the quality of water for consumption.
Keywords: Calidad del agua; compuestos orgánicos; compuestos inorgánicos; metales pesados y plaguicidas